Boosting the air conditioning unit performance using phase change material: Impact of system configuration. (1st December 2022) - Ismail, M.; Zahra, W.K.; Ookawara, Shinichi; Hassan, Hamdy
Abstract: Boosting the energy efficiency of air conditioning (AC) systems will considerably impact on lowering domestic power consumption. Innovative methods are being developed to enhance AC performance. One promising method involves integrating phase change materials (PCM) with the AC systems. The significant PCM charging period is a primary limitation of coupling AC systems with PCM in the previous research. The current study aims to investigate the impact of coupling an AC unit with various PCM container configurations (e.g., parallel plates, staggered and aligned tubes, and elliptical tubes) on PCM charging and discharging, and AC performance. During the nighttime, the low ambient temperature is charged inside the PCMs. Then, during the daytime, the hot ambient air is cooled by passing through the cold PCM heat exchanger before passing over the unit condenser. A complete dynamic mathematical model for the proposed system is constructed and solved numerically using ANSYS software. Results indicate that applying the cylindrical arrangement lowers the solidification time of the PCM at night by approximately one-third compared to the plate arrangement. Also, raising the inflow air temperature of the air-PCM heat exchanger increases the air temperature difference through the heat exchanger and saving percentage of the AC's power and decreases the PCM's charging and discharging time. For inflow air temperatures of 318.15 K, 313.15 K, and 308.15 K, the maximum average percentage of saved power is around 25 %, 18.7 %, and 12.5 %, respectively for 2 h working and around 8.4 %, 7.2 %, and 6.3 %, respectively for 8 h working of the AC unit. Cylindrical configuration is preferable for daily use of AC systems as the charging process can be achieved through the nighttime. Highlights: Impact of air-PCM heat exchanger configuration on AC unit performance is studied. Cylinders configuration is convenient for short-term operation time of the AC unit. Plates and ellipses configurations are best suit for short operation of the AC unit. Highest proportion of power saved by this method is about 25 % for 2 h of AC running.